Prevalence of and reasons for women's, family members', and health professionals' preferences for cesarean section in Iran: a mixed-methods systematic review. - Shirzad, Mahboubeh.; Shakibazadeh, Elham.; Hajimiri, Khadijeh.; Betran, Ana Pilar.; Jahanfar, Shayesteh.; Bohren, Meghan A.; Opiyo, Newton.; Long, Qian.; Kingdon, Carol.; Colomar, Mercedes.; Abedini, Mehrandokht. (Tufts University. Tisch Library., 2021)
Keywords: Cesarean section, Vaginal birth, Qualitative synthesis, Quantitative analysis, Mixed method, Iran.; Springer Open.